The relationship between level of knowledge and medication adherence in hypertensive patients at Pal Tiga Pontianak Health Center - Nurmainah; Ressi Susanti; Asyah Padhilah Safitri (Universitas Muhammadiyah Malang, 2024)
Patient non-adherence to medication use is one of the barriers to successful treatment of hypertension. One of the factors that can affect adherence is knowledge. This study aims to analyze the relationship between knowledge level and medication adherence in outpatient hypertensive patients at the Pal Tiga Pontianak Health Center. This research method is an analytic observational study using a cross-sectional research design. This research was conducted during January-February 2024 with a total of 112 respondents. Data collection used the Hypertension Knowledge-Level Scale (HK-LS) and Adherence to Refill and Medication Scale (ARMS) questionnaire. The results showed that the characteristics of outpatients at Pal Tiga Pontianak Health Center tended to be female (61.6%), aged >45 years (93.8%), not working (72.3%), minimum education level of high school (58.9%), have a high level of knowledge (76.8%) and high level of adherence (56.3%). Chi-square analysis showed no significant relationship between gender (p=0.243), age (p=0.465), and occupation (p=1.000). Meanwhile, there was a significant relationship between the education level (0.012) and the adherence level with the use of antihypertensive drugs. The relationship obtained between the level of knowledge and adherence of hypertensive patients is p=0.044 (p<0.05). The conclusion of this study is that there is a significant relationship between the knowledge level and the adherence level of hypertensive patients at the Pal Tiga Pontianak Health Center